Poorly described phenotypes add to the misfortune of rare diseases - A, Fabre; K, Aouchiche; R, Reynaud (European journal of medical genetics, 2025)
An often overlooked problem in the characterization of rare diseases is the contingent and evolving nature of accepted phenotypes. In the era of next-generation sequencing and genotype-first approaches to patient care, we illustrate the pitfalls of superficial phenotype descriptions via a historic overview of Alagille syndrome. These reflections lead us to a series of recommendations to improve phenotype descriptions, namely to encourage and standardize case reports and create case databases including follow-up data.